Market Competition, Customer Concentration, Company Diversification, and Earnings Quality: Does Integrated Reporting Matter in an Emerging Market? - Bachtiar, Muchamad Izaaz Hannun; Firmansyah, Amrie (Journal of Accounting Research, Organization and Economics, 2022)
Objective This study investigates the association between market competition, customer concentration, corporate diversification, and earnings quality and the role of integrated reporting in moderating these effects within Indonesia's emerging economy.Design/methodology This study employs secondary data from the companys annual reports and financial statements available at www.idx.co.id and the company website. The sample used in this study is 121 manufacturing companies listed on the Indonesian Stock Exchange from 2016 to 2020, which were selected through the purposive sampling method so that 605 observations were obtained. This study engages two-panel data regression models.Results The results suggest that market competition is negatively associated with earnings quality, while customer concentration and corporate diversification are not associated with earnings quality. Furthermore, integrated reporting strengthens the negative effect of corporate diversification on earnings quality. Meanwhile, integrated reporting fails to moderate the impact of market competition and customer concentration on earnings quality.Research limitations/implications Measuring the integrated reporting index score based on the company's annual report, which follows the proxy adopted from the IR reporting framework. No other party has been able to confirm the index results, so the assessment is subjective.Novelty/Originality This study combines the three variables in the context of a company's competitive strategy, which has rarely been conducted, especially in Indonesia. Also, this study employs different proxies, such as the customer concentration proxy referring to Abbasi (2020), Crawford et al. (2020), Deng and Yan (2019), and Kim (2021), in contrast to Aryotama and Firmansyah (2019) who tested tax aggressiveness in Indonesia